A Simple and Sensitive Optode Sensor Glucose Based on Immobilization Benedict Into Nata Cellulose Membranes - Dhony Hermanto; Rochmad Kris Sanjaya; Nurul Ismillayli (Jurnal Pijar Mipa, 2020)
Determination of glucose concentration in urine and blood that anyone can use at any time is Benedict reagent based chemical sensor. This optical sensor was developed by immobilizing Benedict reagent into nata cellulose as supporting material via entrapment. The nata cellulose/Benedict membrane for glucose determination has optimum condition at maximum wavelenghtÃÂ  ÃÂ of 541.57 nm, Benedict concentration of 0.4470 M, and ratio of nata cellulse mass to Benedict volume was 1:3. Characterization of optical sensor for glucose was in working range of 0-5000 ppm, limit of detection was 911,11 ppm, sensitivity was 0.0009 and reproducibility was 0.2295%.